The molecular characterisation of unusual subcutaneous spindle cell lesion of breast. Issue 8 (20th April 2012) - Takano, Elena A; Rogers, Toni-Maree; Young, Richard J; Rayoo, Mukta; Kostos, Phillip; Ferguson, Ross; Campbell, Ian G; Debiec-Rychter, Maria; Fox, Stephen B
Abstract : Background: Spindle cell lesions of the breast represent an interesting diagnostic challenge as they comprise a wide range of tumours that are rare. Differentiating dermatofibrosarcoma protuberans (DFSP) from other dermatofibromas using CD34 immunohistochemistry alone is difficult; therefore, fluorescence in situ hybridisation (FISH) analysis is often employed to identify typical COL1A1–PDGFB fusion or gene rearrangement. Although molecular confirmation of diagnosis is unnecessary in the majority of DFSP cases, the detection of chromosomal rearrangement is valuable in tumours that show unusual clinicopathological features as in this study the authors report a case of DFSP of breast that did not show any typical known molecular features. Methods and results: Morphological and immunohistochemical study was highly suggestive of the diagnosis of DFSP. To further investigate this case, DNA copy number alterations were investigated by the 250 K Affymetrix SNP Mapping array. DNA analysis did not show any of the known translocations reported in DFSP or any known solid tumour category. However, in addition to copy number changes on chromosome 1, amplification of chromosome 7p which contains the epidermal growth factor receptor ( EGFR ) gene was observed. Results from EGFR FISH showed an increase in EGFR gene to chromosome 7 ratio (3:1) suggesting amplification of the EGFR gene. Conclusion: This case of an unusual DFSP demonstrates that genomic interrogation provides additional potential targets such as a therapeutic avenue with anti- EGFR therapies and shows the power of molecular characterisation of unusual tumours for a personalised medicine approach.